Tribochemistry of organic friction modifiers in lubrication of bio-hydrogenated diesel - Paweekan Hansungnoen; Ekarong Sukjit; Anawat Phatthanaphon; Atthaphon Maneedaeng (Cleaner Engineering and Technology)
Global energy security and environmental concerns have driven the advancement of renewable fuel technologies. Bio-hydrogenated diesel (BHD), produced via catalytic hydrogenation of biomass feedstocks, exhibits combustion characteristics comparable to those of petroleum-based diesel. However, the removal of oxygen-containing compounds during production significantly reduces its boundary lubricity, leading to increased friction and wear in fuel injection systems. This study systematically investigates the influence of molecular structure on the tribological performance of organic friction modifiers (OFMs) in BHD, with a focus on functional group effects and hydrocarbon chain configuration. Using high-frequency reciprocating rig (HFRR) testing in accordance with ISO 12156–1:2018, friction coefficients and wear scar diameters were measured for five distinct OFMs at concentrations ranging from 0.1 to 1.0 % by weight. A multi-technique surface analysis-including 3D laser microscopy, SEM-EDS, and FT-IR spectroscopy-was conducted to characterize lubrication film formation and tribochemical interactions. The findings reveal that carboxyl-functionalized OFMs, particularly stearic acid, achieved the highest tribological efficiency, reducing the friction coefficient by 57 % (from 0.296 to 0.126) and the wear scar diameter by 70 % (from 515 μm to 155 μm) compared to pure BHD. A clear hierarchical ranking of functional group effectiveness in reducing friction and wear was established: COOH > –CONH2 > –OH > –COOR, with polar head group chemistry playing a more dominant role than hydrocarbon tail configuration. Additionally, the study highlights the effect of molecular structure, demonstrating that saturated OFMs (stearic acid) outperformed unsaturated counterparts (oleic acid) due to their ability to form compact, cohesive boundary films, resulting in 13 % lower friction and 9 % smaller wear scars. These findings provide molecular-level design insights for optimizing OFMs in paraffinic biofuels, supporting the development of next-generation additives to enhance BHD lubricity and engine durability.